The Examined Life: On the Formation of Souls and Schooling. (April 2013) - Allen, Ansgar
The spread of examination throughout educational institutions is often viewed as an overly constraining influence, one that distorts pedagogic relationships and prevents more genuine educational activities from taking place. This critique of examination ignores the extent to which the structure of the school and the soul of the child are already constituted by examining techniques. A survey of the 19th-century emergence of mass schooling shows that examining techniques have long been embedded in schools. The early development of mass schooling incorporated two distinct and enduring approaches to the formation of souls: disciplinary and pastoral examination. These examining practices would help construct the kind of self-governing subjectivities required by the nation-state. Those who seek to confront practices of examination today face a task that is far more demanding than it first appears. This confrontation would involve nothing less than a rigorous and wide-ranging critique of how examination and schooling in their various forms continue to assemble us as subjects of power.